SYSTEMATIC INTEGRATION OF CRITICAL THINKING IN GRADES 5–9 EFL CLASSROOMS: A PEDAGOGICAL FRAMEWORK BASED ON THE “GUESS WHAT!” COURSEBOOKS - Ahmadjonova Diyorakhon Dilshod kizi (Modern American Journals, 2025)
This article explores how critical thinking skills can be systematically integrated into English as a Foreign Language (EFL) lessons for learners in grades 5–9 through the pedagogical use of coursebooks. Recognising the growing importance of critical thinking in language education, the study addresses the challenge of embedding higher-order thinking into everyday classroom practice, particularly in lower secondary education. Adopting a qualitative, framework-development design, the study analyses the “Guess What!” coursebook series to identify opportunities for critical thinking and examines how these can be pedagogically organised through lesson staging and teacher scaffolding. The findings reveal that while the coursebooks contain implicit cognitive potential, critical thinking remains fragmented without a structured instructional approach. In response, the article proposes a pedagogical framework that aligns recurring lesson stages with progressively complex critical thinking skills across grades 5–9. The framework emphasises developmental progression, teacher mediation, and the systematic use of existing tasks. The study contributes a practical, material-based model that supports the integration of critical thinking into EFL instruction and offers implications for classroom practice and teacher education in comparable educational contexts.
Keywords: Critical thinking; EFL instruction; coursebook-based pedagogy; Guess What!; lower secondary education; pedagogical framework.